2020
DOI: 10.3389/fvets.2020.00556
|View full text |Cite
|
Sign up to set email alerts
|

Chagas Disease in Pregnant Women in the Peruvian Amazon Basin. Cross-Sectional Study

Abstract: Aims: To assess the prevalence of Chagas disease in pregnant women in Iquitos City, Peru. Material and Methods: Cross-sectional survey in 300 pregnant women in Iquitos (Peru) from 1 May 2019 to 15 June 2019. Women were tested using an ELISA serology test. Results: Serology was positive in one case (prevalence: 0.33%; 95% confidence interval: 7.1–13.9%), of a 25-year-old woman who lived in a wooden house with a leaf roof in a periurban area of Iquitos. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“… 12 , 13 , 38 Secondly, due to the low endemicity in Sao Paulo and Lima, the main districts of origin of Brazilians and Peruvian respectively, a larger number of participants would be necessary to showcases. 39 , 40 , 41 , 42 The results showed that the screening is cost-effective until a prevalence of 0.43%, supporting the inclusion of Bolivians and Peruvians. On the other hand, a country base screening has several disadvantages.…”
Section: Discussionmentioning
confidence: 84%
“… 12 , 13 , 38 Secondly, due to the low endemicity in Sao Paulo and Lima, the main districts of origin of Brazilians and Peruvian respectively, a larger number of participants would be necessary to showcases. 39 , 40 , 41 , 42 The results showed that the screening is cost-effective until a prevalence of 0.43%, supporting the inclusion of Bolivians and Peruvians. On the other hand, a country base screening has several disadvantages.…”
Section: Discussionmentioning
confidence: 84%
“…Ramos-Rincón y cols., en su estudio sobre la EC en mujeres embarazadas de la Cuenca Amazónica Peruana utilizaron dos estuches comerciales: Chagatest ELISA con lisado de T. cruzi (Weiner, Rosario, Argentina) y Chagatest ELISA recombinante (Weiner, Rosario, Argentina), detectaron 4 casos positivos por ELISA recombinante, de los cuales sólo uno resultó positivo por ELISA que utilizó lisado, y 3 muestras como no concluyentes. Reportaron una seroprevalencia de anticuerpos anti-T. cruzi de 0,33% 31 , muy similar a lo reportado en el presente estudio al utilizar las 3 pruebas serológicas en serie (0,43%).…”
Section: Discussionunclassified
“…No obstante, no contamos con estudios epidemiológicos concluyentes. En un estudio reciente realizado en 300 mujeres embarazadas publicado por nuestro grupo, se identificó una paciente con la enfermedad asintomática (5) .…”
Section: Sr Editor La Enfermedad De Chagas (Ec) Está Causada Porunclassified
“…However, we do not have conclusive epidemiological studies. In a recent study of 300 pregnant women published by our group, one patient with asymptomatic disease was identified 5 .…”
mentioning
confidence: 99%